Neuroendocrine tumor in gastric adenoma: a diagnostic pitfall mimicking invasive adenocarcinoma - Lee Sun-Mi; Ahn Soomin; Lee Yun; Jang Kee-Taek; Park Cheol; Kim Kyoung-Mee (BMC, 2012)
Abstract Neuroendocrine tumor (NET) in adenoma of the gastrointestinal tract is a rare mixed glandular-endocrine neoplasm and has uncommonly been described mostly in the colon. Histologically, this tumor is composed of a predominant proportion of benign adenomatous component and a small portion of well-differentiated NE component. Only three cases of NET in gastric adenoma have been reported in the literature. We present 4 cases of NET in gastric adenoma mimicking invasive adenocarcinoma. The NETs were 0.62 mm to 4.1 mm in size and located at the basal lamina propria, muscularis mucosa and submucosa. Histologically, NETs consisted of nests, cords, tubules, and clusters of cells that predominantly interposed between the foveolar base without disturbing the overall polyp architecture. The lesions were completely removed by endoscopic submucosal dissection in three cases and in one case, subtotal gastrectomy was performed because endoscopic biopsy was invasive adenocarcinoma. The patients' clinical course was uneventful without an evidence of recurrence or metastasis. The recognition of NET in gastric adenoma will help avoid potential diagnostic pitfalls masquerading as invasvie adenocarcinomas posed by their infiltrative pattern into submucosa. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1688552293761001